113 Immunological Effects of Ganoderma Lucidum Supplementation in Canine Nutrition. (21st September 2022) - Kayser, Emanuela; He, Fei; Gomez, Luis M; de Godoy, Maria R
Abstract: Ganoderma lucidum (GL) is a mushroom that has been widely used in Asia for its immunomodulatory, anti-inflammatory and anti-tumor capacity in humans. However, the nutraceutical properties of GL have not been tested in dogs. Forty adult beagles were used in a completely randomized design and were fed a commercial dry extruded complete and balanced diet plus GL top-dressed daily upon feeding time. Four experimental treatments were used: 0% GL supplementation (control), 5 mg/ kg BW of GL, 10 mg/ kg BW of GL, or 15 mg/kg BW of GL. Following a 7 d adaptation to the control diet, dogs were fed their respective treatment diets for consecutive 28 d. They were challenged with vaccination of a modified live virus Canine Distemper, Adenovirus Type 1 (Hepatitis), Adenovirus Type 2, Parainfluenza, and Parvovirus and killed Rabies Virus on d 7 with blood collections on d 0, 14, and 28. The objective of the present study was to evaluate the effects of dietary inclusion of GL on peripheral blood mononuclear cells (PBMC; T-cells, B-cells, monocytes, and natural killers) and vaccine titers response of adult dogs. The inclusion of GL in all dosages was well-accepted by all dogs. There was a trend that the percentage of MHC-II from B-cells was greater in dogs fed 15 mg/kg of GL (41.91%) compared with the control group (34.63%). The phagocytosis response tended to have treatment by time interaction among treatments; dogs fed 15mg/kg of GL tended to have greater phagocytosis activity on d 28 than dogs from the control group and dogs fed 5mg/kg of GL. These data suggest that the inclusion of GL had no detrimental effects on analyzed PBMC. Based on our findings, GL may also exert beneficial immunomodulatory effects in healthy adult dogs when provided at a daily dose of 15 mg/ kg BW.